Purinergic receptors in embryonic and adult neurogenesis. (May 2016) - Oliveira, Ágatha; Illes, Peter; Ulrich, Henning
Abstract: ATP (adenosine 5′-triphosphate), one of the most ancient neurotransmitters, exerts essential functions in the brain, including neurotransmission and modulation of synaptic activity. Moreover, this nucleotide has been attributed with trophic properties and experimental evidence points to the participation of ATP-activated P2X and P2Y purinergic receptors in embryonic brain development as well as in adult neurogenesis for maintenance of normal brain functions and neuroregeneration upon brain injury. We discuss here the available data on purinergic P2 receptor expression and function during brain development and in the neurogenic zones of the adult brain, as well as the insights based on the use of in vitro stem cell cultures. While several P2 receptor subtypes were shown to be expressed during in vitro and in vivo neurogenesis, specific functions have been proposed for P2Y1, P2Y2 metabotropic as well as P2X2 ionotropic receptors to promote neurogenesis. Further, the P2X7 receptor is suggested to function in the maintenance of pools of neural stem and progenitor cells through induction of proliferation or cell death, depending on the microenvironment. Pathophysiological actions have been proposed for this receptor in worsening damage in brain disease. The P2X7 receptor and possibly additional P2 receptor subtypes have been implicated in pathophysiology of neurological diseases including Parkinson's disease, Alzheimer's disease and epilepsy. New strategies in cell therapy could involve modulation of purinergic signaling, either in the achievement of more effective protocols to obtain viable and homogeneous cell populations or in the process of functional engraftment of transplanted cells into the damaged brain. This article is part of the Special Issue entitled 'Purines in Neurodegeneration and Neuroregeneration'. Highlights: Purinergic signaling is present throughout nervous system development. P2Y1 receptors in neural progenitor migration are important in cortical layer development. P2X7 receptors act as dual sword, promoting proliferation or inducing cell death. P2X7 receptors are overexpressed in neurodegenerative diseases. P2X7 receptor inhibition is neuroprotective and enhances stem cell engraftment.